Early and Late Protective Effect of Bone Marrow Mononuclear Cell Transplantation on Radiation-Induced Vascular Dysfunction and Skin Lesions. Issue 1 (January 2019) - Holler, Valérie; Buard, Valerie; Roque, Telma; Squiban, Claire; Benderitter, Marc; Flamant, Stephane; Tamarat, Radia
Skin lesions caused by accidental exposure to radiation or by radiotherapy are a major clinical challenge. We evaluated the effect of bone marrow mononuclear cells (BMMNC) on collagen remodeling and vascular function in radiation-induced skin lesions in the acute and late phases in mice. We studied the effect of BMMNC transplantation in a mouse model of cutaneous radiation injury combining local skin gamma-irradiation and biopsy punch wound. Mice were first irradiated, punched and then BMMNC were intramuscularly administered. Seven days after injury, BMMNC promoted wound healing by (i) increasing re-epithelialization, tissue collagen density and mRNA levels of collagens 1A1, 1A2, and 3A1, and (ii) inhibiting the radiation-induced vascular activation and limiting interactions between leukocytes and the vascular endothelium compared with control. Importantly, BMMNC did not amplify the inflammatory response despite the infiltration of neutrophils and macrophages associated with the expression of IL-6 and MCP-1 mRNAs in the tissue. Remarkably, the beneficial effects of BMMNC therapy on matrix remodeling were maintained for 2 months. Furthermore, BMMNC injection restored vascular function in skin tissue by increasing vascular density and vascular permeability. This therapeutic strategy based on BMMNC injection protects against radiation-induced skin lesions by preventing vascular dysfunction and unfavorable remodeling in the acute and late phases.